1988
DOI: 10.1007/bf00442609
|View full text |Cite
|
Sign up to set email alerts
|

Di-(2-ethylhexyl)-phthalate as plasticizer in PVC respiratory tubing systems: indications of hazardous effects on pulmonary function in mechanically ventilated, preterm infants

Abstract: Several PVC medical devices contain the plasticizer Di-(2-ethylhexyl)-phthalate (DEHP) in high concentration. Taken systematically DEHP only has minor toxic effects in the human organism. In three preterm infants artificially ventilated with PVC respiratory tubes unusual lung disorders resembling those observed in hyaline membrane disease, verified both clinically and radiologically, were observed during the fourth week of life. It was assumed that these lung disorders were causally related to the exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 34 publications
3
48
0
1
Order By: Relevance
“…21 Clinical presentation was similar to that noted with bronchopulmonary disease. Two infants exhibited episodes of respiratory deterioration associated with high concentrations of DEHP extracted from respiratory circuit condensate.…”
Section: Human Studiessupporting
confidence: 61%
“…21 Clinical presentation was similar to that noted with bronchopulmonary disease. Two infants exhibited episodes of respiratory deterioration associated with high concentrations of DEHP extracted from respiratory circuit condensate.…”
Section: Human Studiessupporting
confidence: 61%
“…Hillman et al 1975;Latini 2000;Latini and Avery 1999;Loff et al 2000;Plonait et al 1993;Tickner et al 2001). Thus, it is conceivable that prenatal and postnatal exposures may have synergistic and cumulative actions in producing adverse neonatal effects, especially for premature infants with very low birth weight (Roth et al 1988). …”
Section: Discussionmentioning
confidence: 99%
“…Because of the cross-sectional nature of these studies, we cannot determine if concentrations of phthalates in the home are also involved in the development of atopic diseases. In a study conducted in pre-term infants with polyvinyl chloride (PVC) respiratory tubing, Roth et al (1988) found these infants to have clinically and radiologically confirmed hyaline membrane disease, which was hypothesized to be caused by the DEHP exposure. Di(2-ethylhexyl) phthalate was also found in the lung tissue of one of the patients who died of a pneumothorax soon after birth (Roth et al 1988).…”
Section: Phthalates (A) Exposurementioning
confidence: 99%